AI in medical training: how smarter learning creates safer doctors - Abdul Ghani, Azril Shahreez (Paradigm Scitech Solution, 2025)
In 2023, a global report estimated that the body of medical knowledge now doubles every 73 days. For medical students, this rapid expansion can feel overwhelming. They are expected not only to keep up with new discoveries but also to develop the sharp decision-making skills required of future doctors (Ananthakrishnan, 2020).To cope, medical schools have long used strategies like spaced learning and active recall, which help students remember information for longer and perform better in exams (Chugh & Tripathi, 2020; Csaba et al., 2025). But medicine is about much more than memorising facts. Doctors also need to make the right calls under pressure, sometimes relying on quick instincts and other times slowing down to carefully weigh the evidence. That balance is hard to teach in a classroom.